The interaction between rs 3,807,992 genotypes with the dietary inflammatory index on Leptin, Leptin resistance, and Galectin 3 in obese and overweight women - Farideh Shiraseb; Mena Farazi; Niloufar Rasaei; Cain C. T. Clark; Shahin Jamili; Khadijeh Mirzaei (BMC Endocrine Disorders, 2022)
Abstract Objective Obesity is related to increasing leptin and some inflammatory factors that are associated with low-grade inflammation. Moreover, several studies have shown Caveolin-1 (CAV1) genetic variations may be associated with dietary intake. The current study aimed to evaluate the interaction of CAV1 rs3807992 with types of the energy-adjusted dietary inflammatory index (EDII) in leptin, leptin resistance, and Galectin 3, as inflammatory factors. Methods This cross-sectional study was carried out on 363 overweight and obese females. Dietary intake and DII were obtained from a 147-item food frequency questionnaire (FFQ). The CAV-1 genotype was measured using the PCR-RFLP method. Anthropometric values and serum levels of leptin and Galectin 3 were measured by standard methods. Results Increased adherence to EDII in the interaction with CAV1 genotypes led to an increase in leptin level 79.15 (mg/l) (β = 79.15, CI = − 1.23,163.94, P = 0.04) in model 3, after controlling for further potential confounders. By contrast, adherence to EDII in the interaction with the genotype including risk alleles showed no significant interaction, even after adjustment in model 3 (β = 0.55, CI = − 0.99, 2.09, P = 0.48). Although, a marginal positive significant interaction was found between EDII and CAV1 genotypes on Galectin 3, after adjustment in model 3 (β = 31.35, CI = 0.13, 77.13, P = 0.05). Conclusions The present study indicates that a high adherence of EDII and CAV1 genotypes containing risk alleles may be a prognostic factor and increase both leptin and Galectin3. However, it seems that the presence of interaction was not on leptin resistance. Further functional studies are necessary to elucidate the exact mechanism.